Axion star collisions with black holes and neutron stars in full 3D numerical relativity - Clough, K; Dietrich, T; Niemeyer, J (American Physical Society, 2018)
Axions are a potential dark matter candidate, which may condense and form self-gravitating compact objects, called axion stars (ASs). In this work, we study for the first time head-on collisions of relativistic ASs with black holes (BHs) and neutron stars (NSs). In the case of BH-AS mergers we find that, in general, the largest scalar clouds are produced by mergers of low compactness ASs and spinning BHs. Although in most of the cases which we study the majority of the mass is absorbed by the BH within a short time after the merger, in favorable cases the remaining cloud surrounding the final BH remnant can be as large as 30% of the initial axion star mass, with a bosonic cloud mass of O ( 10 − 1 ) M BH and peak energy density comparable to that obtained in a superradiant buildup. This provides a dynamical mechanism for the formation of long lived scalar hair, which could lead to observable signals in cases where the axion interacts with baryonic matter around the BH, or where it forms the seed of a future superradiant buildup in highly spinning cases. Considering NS-AS collisions we find two possible final states: (i) a BH surrounded by a (small) scalar cloud, or (ii) a stable NS enveloped in an axion cloud of roughly the same mass as the initial AS. While for low mass ASs the NS is only mildly perturbed by the collision, a larger mass AS gives rise to a massive ejection of baryonic mass from the system, purely due to gravitational effects. Therefore, even in the absence of a direct axion coupling to baryonic matter, NS-AS collisions could give rise to electromagnetic observables in addition to their gravitational wave signatures.